Proceedings of the 2012 IEEE/ACM International Symposium on Nanoscale Architectures 2012
DOI: 10.1145/2765491.2765521
|View full text |Cite
|
Sign up to set email alerts
|

A novel write-scheme for data integrity in memristor-based crossbar memories

Abstract: The memristor is one among the most promising emerging technologies for enabling a new generation of Non Volatile Memories. The memristor operates faster than a Phase Change Memory (PCRAM) and has a simpler structure than a magnetic memory (MRAM), while making possible the design of cross-point structures in crossbars at very high density. The presence of sneak path currents however causes an increase in power consumption and a reduction in data integrity and performance. To overcome this issue a novel write m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Date write operation is a challenging task in memristors due to the unwanted current paths and memristive state-based response. Ruotolo et al [70] suggested that a memristorbased memory can be much more faster than a phase change memory and much simpler than a magnetic memory. To mitigate issues in write operation, researchers proposed a memristor-based write operation for the memory operations.…”
Section: Data Write Operation In Tcammentioning
confidence: 99%
See 1 more Smart Citation
“…Date write operation is a challenging task in memristors due to the unwanted current paths and memristive state-based response. Ruotolo et al [70] suggested that a memristorbased memory can be much more faster than a phase change memory and much simpler than a magnetic memory. To mitigate issues in write operation, researchers proposed a memristor-based write operation for the memory operations.…”
Section: Data Write Operation In Tcammentioning
confidence: 99%
“…Hybrid architectures [97] Electronic neurons [100] Von Neumann vs Neuromorphic arch. [110] Write operation [70] Dynamic route prefix memories [49][50]…”
Section: Architectures Reservoir Computation Memristive Propertiesmentioning
confidence: 99%
“…Many prior researches have focused over the use of memristors for the development of energy efficient TCAM architectures. Some of the research areas in the design of memristor-based TCAM architecture include TCAM cell designing [4], managing storage operations [5], [6], performing search functions [7] and computing read and write operations efficiently [1]. The studies in these research areas showcased the effectiveness of memristors in conserving energy at the same processing rate of one clock cycle.…”
Section: Background and Related Workmentioning
confidence: 99%
“…They proposed a fuzzy look up functionality to measure the memristor states in the M-CAM architecture. In [26], Ruotolo et al addressed the search operation challenges in the memristor-based TCAM. They showed that the memristor-based TCAM can provide power efficiency at the cost of less precision in the data storage mode as compared to the PCMs and magnetic memories.…”
Section: Related Workmentioning
confidence: 99%